Service user perspectives on coercion and restraint in mental health. (2nd January 2018) - Rose, Diana; Perry, Emma; Rae, Sarah; Good, Naomi
Abstract : Coercion remains a central aspect of many people's mental healthcare. It can include the use of legislation to restrict freedoms, the use of physical restraint, the restriction of freedom of movement and/or association, and the forced or covert administration of medication. There is good evidence that the use of such measures can traumatise service users. This article reports the findings of a survey of service users regarding their experiences of coercion and restraint and embeds this in the wider international and institutional environment.